The Implementation of a Fast-folding Pipeline for Long-period Pulsar Searching in the PALFA Survey - Parent, E.; Kaspi, V. M.; Ransom, S. M.; Krasteva, M.; Patel, C.; Scholz, P.; Brazier, A.; McLaughlin, M. A.; Boyce, M.; Zhu, W. W.; Pleunis, Z.; Allen, B.; et al. (The Astrophysical journal, 2018)
The Pulsar Arecibo L-Band Feed Array (PALFA) survey, the most sensitive blind search for radio pulsars yet conducted, is ongoing at the Arecibo Observatory in Puerto Rico. The vast majority of the 180 pulsars discovered by PALFA have spin periods shorter than 2 s. Pulsar surveys may miss long-period radio pulsars owing to the summing of a finite number of harmonic components in conventional Fourier analyses (typically ∼16), or as a result of the strong effect of red noise at low modulation frequencies. We address this reduction in sensitivity by using a time-domain search technique: the fast-folding algorithm (FFA). We designed a program that implements an FFA-based search in the PALFA processing pipeline and tested the efficiency of the algorithm by performing tests under both ideal, white-noise conditions, as well as with real PALFA observational data. In the two scenarios, we show that the time-domain algorithm has the ability to outperform the FFT-based periodicity search implemented in the survey. We perform simulations to compare the previously reported PALFA sensitivity with that obtained using our new FFA implementation. These simulations show that for a pulsar having a pulse duty cycle of roughly 3%, the performance of our FFA pipeline exceeds that of our FFT pipeline for pulses with dispersion measure 40 pc cm−3 and for periods as short as ∼500 ms, and that the survey sensitivity is improved by at least a factor of two for periods 6 s. Early results from the implementation of the algorithm in PALFA, including discoveries, are also presented in this paper.